Adnexal mass in pregnancy - Sandoval Díaz, Ither (2019)
Literature on adnexal masses during pregnancy recommend ultrasonography for initial diagnosis; benign cysts represent the most common findings. Expectant management is considered in most cases, but the surgical approach is recommended when malignancy is suspected or when the mass affects pregnancy. Nowadays, the best approach is laparoscopic surgery with advantages that include minimal invasion.